Problems of Granting Mining Business Permits to Community Organizations - Rosyadi, Safriansyah Yanwar; Sara, Rineke (Cognitionis Civitatis et Politicae, 2025)
Granting mining business permits (IUP) to community organizations in Indonesia faces various challenges that hinder the effectiveness of such policies because related to unclear regulations, overlapping authority between government institutions, and limited monitoring and support capacity. This research aims to analyze the factors influencing the granting of mining permits to community organizations and identify the obstacles in the process. A qualitative approach was used, with in-depth interviews involving stakeholders such as government officials, mining entrepreneurs, and community organization members. The findings reveal that unclear licensing procedures, lack of transparency, and limited community understanding of regulations are the main factors hindering the effective issuance of mining permits. Moreover, the involvement of local communities in the oversight and management of mining operations remains limited. The conclusion of this study suggests that regulatory reform and the enhancement of human resource capacity at the local level are necessary to improve the permitting process. Collaboration between the government, communities, and the private sector is crucial to creating a transparent, accountable, and sustainable permitting system.